The body image: taking an evaluative stance towards semiotic resources. Issue 2 (3rd April 2021) - Busch, Brigitta
ABSTRACT: In the current revival of Gumperz' notion of the verbal repertoire, which today is rather termed as communicative or semiotic repertoire, some scholars tend to locate repertoires with individual speakers whereas others see them primarily as emerging from particular spatial arrangements. What is often underestimated in both approaches is the importance of the bodily and emotionally lived experience of communicative interaction. This experience, however, can be critical in preventing resources from being deployed even though they are individually available and appropriate to the situation as well as in mobilising unexpected resources to achieve understanding. Conceiving the repertoire as holding an intermediate and mediating position between situated interactions, (sometimes competing) discourses, and subjects' lived experiences of communicating, in this paper, I examine the interplay of these instances by introducing the notion of the 'body image': an imaginary, affectively loaded representation of the own body in relation to others. Finally, I discuss the language portrait (in which participants visualise their semiotic resources with reference to the outline of a body silhouette) as a window onto the body image and as a method to empirically investigate how people evaluate their resources and position themselves with regard to ideologies of communication.